The Influence of the Implementation of Financial Information Systems in Credit Cooperatives on the Quality of Financial Reports in the San Dominggo Hokeng KSP Kopdit and Ikamala KSP Kopdit Cooperatives - Lewar, Sesilia Ekarista; Sanga, Konstantinus Pati; Dilliana , Siktania Maria; Noeng, Amanda Yecci (International Publisher (YAPENBI), 2025)
This study aimed to analyze the influence of implementing credit cooperative financial information systems on the quality of cooperative financial reports, using a case study at KSP Kopdit San Dominggo Hokeng and KSP Kopdit Ikamala. The research data were obtained from primary sources using questionnaires distributed to 42 respondents from both cooperatives. The data analysis method used in this study was simple regression analysis, and hypothesis testing was conducted using the t-test. The descriptive analysis result showed that the variable of the credit cooperative financial information system in KSP Kopdit San Dominggo Hokeng and KSP Kopdit Ikamala was categorized as “Very Good” with an average score of 90,63. Likewise, the variable of financial report quality was categorized as “Very Good” with in average score of 88,2. The statistical result of the t-test indicated that the financial information system had a significant effect on the quality of financial reports. This means that an improvement in the financial information system could significantly enhance the quality of cooperative financial reports.